If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(z + 2) = 25 Reorder the terms: 5(2 + z) = 25 (2 * 5 + z * 5) = 25 (10 + 5z) = 25 Solving 10 + 5z = 25 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5z = 25 + -10 Combine like terms: 10 + -10 = 0 0 + 5z = 25 + -10 5z = 25 + -10 Combine like terms: 25 + -10 = 15 5z = 15 Divide each side by '5'. z = 3 Simplifying z = 3
| 7-3x=y | | 2345x-23167=3 | | 747-60x=147 | | 25z+5-8=147 | | 0.4-1.2=0.3r+0.6 | | 8q=32 | | 7(-2x+10)=42 | | 8(2-5x)=-264 | | 11.3+-7.2=3.82 | | 747-60x=0 | | 4y+5(5+y)=-2 | | ax+by=0 | | 2(-4r+2)=-6(-8+2r) | | .53y+2.5=5.1 | | -88+9z=z | | 3xz+4-8=1 | | 2(4d+5h)-(9h-5d)= | | 2x+1+4x+4=4 | | 7u-22=-1 | | -8(6x+5)=-520 | | 4h+7=4h | | x+3=30 | | 220+0.15x=368.50 | | (3x^2y+7xy^2)(x^2y^3-2y^2)= | | 11=1+8m+2n | | -5x-10=2-(x-4) | | 3(2+e)-4e=e+16 | | 9.1x+23.1=-4.2 | | (5x^5y^4)(2x^5y)= | | 21b=-19 | | 7(4x-2)=322 | | 112=4x+6(x+7) |